2019
DOI: 10.1038/s41467-019-10113-3
|View full text |Cite
|
Sign up to set email alerts
|

Form vision from melanopsin in humans

Abstract: Detection and discrimination of spatial patterns is thought to originate with photoreception by rods and cones. Here, we investigated whether the inner-retinal photoreceptor melanopsin could represent a third origin for form vision. We developed a 4-primary visual display capable of presenting patterns differing in contrast for melanopsin vs cones, and generated spectrally distinct stimuli that were indistinguishable for cones (metamers) but presented contrast for melanopsin. Healthy observers could detect sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 40 publications
3
68
0
2
Order By: Relevance
“…Given the capacity of at least some ipRGCs to act as irradiance detectors (Dacey et al, 2005;Wong et al, 2005;Schmidt and Kofuji, 2009;Davis et al, 2015;Storchi et al, 2015), their intra-retinal connectivity has been considered as a mechanism for adjusting retinal function according to ambient light levels. Accordingly, there is evidence of ipRGC influences over visual response characteristics in both mice and humans (Hankins and Lucas, 2002;Allen et al, 2014;Allen and Lucas, 2016;Milosavljevic et al, 2018;Allen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Given the capacity of at least some ipRGCs to act as irradiance detectors (Dacey et al, 2005;Wong et al, 2005;Schmidt and Kofuji, 2009;Davis et al, 2015;Storchi et al, 2015), their intra-retinal connectivity has been considered as a mechanism for adjusting retinal function according to ambient light levels. Accordingly, there is evidence of ipRGC influences over visual response characteristics in both mice and humans (Hankins and Lucas, 2002;Allen et al, 2014;Allen and Lucas, 2016;Milosavljevic et al, 2018;Allen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the discovery of melanopsin expressing intrinsically photosensitive ganglion cells (ipRGCs) [32][33][34][35][36][37] in the inner retina which contributed fundamentally to the understanding of visual processing 34,[38][39][40][41][42] , form vision 43 , brightness perception [44][45][46][47][48][49][50] , circadian photoentrainment 37,[51][52][53] and pupil light response [54][55][56][57] . There are six different subtypes 58,59 of ipRGCs projecting to the olivary pretectal nucleus 36,41 (OPN), the dorsal lateral geniculate nucleus 43,60,61 (LGN) and the suprachiasmatic nucleus 42,62 (SCN) of the hypothalamus. The so-called M1 ipRGCsubtypes are part of the primary afferent pupillary pathway which controls the pupil aperture through the OPN and the Edinger-Westphal nucleus 63,64 .…”
mentioning
confidence: 99%
“…). Further support for the contribution of melanopsin to human vision is provided by recent evidence that spatial patterns that were spectrally indistinguishable for cones but had contrast for melanopsin could be discriminated by healthy human subjects(Allen et al, 2019). Likewise an fMRI study in four healthy subjects demonstrated that high contrast melanopsin-specific light stimuli elicited a response in the primary visual cortex, associated with a brightening of visual perception(Spitschan et al, 2017).…”
mentioning
confidence: 95%
“…those functions of light that are not directly related to image-formation, such as circadian rhythm photoentrainment, pupillary light reflex, melatonin suppression, as well as the regulation of alertness, sleep and cognition (Gooley et al, 2012;Sand et al, 2012;Gaggioni et al, 2014). Recent evidences also support an involvement of mRGCs in visual processes, such as brightness detection and coarse image formation (Hankins et al, 2008;Ecker et al, 2010;Gooley et al, 2012;Sand et al, 2012;Gaggioni et al, 2014;Allen et al, 2019). mRGCs main central projections include the hypothalamic suprachiasmatic nucleus (SCN), site of the master circadian clock, the hypothalamic preoptic area implicated in sleep initiation, the olivary pretectal nucleus regulating pupil size, the medial amygdala, part of the olfactory and emotional response (Hattar et al, 2006;Hannibal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%